Effects of the implementation of integrative and complementary practices in public health policies: Literature review (Research, Society and Development, 2023)
This article aims to discuss and problematize the difficulties faced in the effective implementation of the National Policy on Integrative and Complementary Practices (PNPIC) in health services. The method chosen for the construction of this study was an integrative review. As a result, 39 articles were analyzed and organized by reading their titles and abstracts. When appropriate to the objectives of the work, the articles were read and analyzed in full and subsequently organized into thematic categories. Thus, it was concluded that, given the considerations presented throughout this work, the difficulty of implementing the PNPIC in the entirety of the Unified Health System (SUS) is visible due to the absence of well-defined strategies aligned with public policies.